2017
DOI: 10.14723/tmrsj.42.139
|View full text |Cite
|
Sign up to set email alerts
|

Emission characteristics of ZnO-TiO<sub>2</sub> upconversion scintillator containing Er<sup>3+</sup> and Yb<sup>3+</sup> using MOD method

Abstract: The metal organic decomposition (MOD) method enables the coating of any oxide material via atmospheric baking of a solution applied to a substrate and enables the fabrication of thin films via simple processes such as using spin coaters. We used titanium oxide, zinc oxide (ZnO), ytterbium oxide, and erbium oxide as MOD solutions. We mixed Ti, Zn, Yb, and Er at arbitrary mixing ratios, applied them on substrates, and then heated them at 1000°C for 4 h under atmosphere. We found that the maximum value for lumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…As the content of Yb is reduced, the emission intensities changed at 555 nm ( 4 S 3/2 → 4 I 15/2 ) and 672 nm ( 4 F 9/2 → 4 I 15/2 ). Our past study examined the energy-transfer process in detail [31]. In Yb and Er doped samples, the emission intensities of the green component at 555 nm ( 4 S 3/2 → 4 I 15/2 ) are close to each other.…”
Section: Emission Characteristicsmentioning
confidence: 76%
See 2 more Smart Citations
“…As the content of Yb is reduced, the emission intensities changed at 555 nm ( 4 S 3/2 → 4 I 15/2 ) and 672 nm ( 4 F 9/2 → 4 I 15/2 ). Our past study examined the energy-transfer process in detail [31]. In Yb and Er doped samples, the emission intensities of the green component at 555 nm ( 4 S 3/2 → 4 I 15/2 ) are close to each other.…”
Section: Emission Characteristicsmentioning
confidence: 76%
“…Yb and Er oxides were adopted as doping materials. In reference to Luitel et al [30], our previous work identified the best molar ratio for this UC phosphor as Ti/Zn/Yb/Er=1/1/0.06/0.02 is best [31]. However, to increase the luminescence efficiency, each element of the metal oxide must be analyzed in more detail.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation